2019
DOI: 10.3389/fbioe.2019.00318
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Niche in Lung Alveolar Development, Homeostasis, and Regeneration

Abstract: Endothelial cells (ECs) constitute small capillary blood vessels and contribute to delivery of nutrients, oxygen and cellular components to the local tissues, as well as to removal of carbon dioxide and waste products from the tissues. Besides these fundamental functions, accumulating evidence indicates that capillary ECs form the vascular niche. In the vascular niche, ECs reciprocally crosstalk with resident cells such as epithelial cells, mesenchymal cells, and immune cells to regulate development, homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 186 publications
1
43
0
Order By: Relevance
“…We used Tie2-specific Twist1 knockout mice in this study and found that Twist1 knockdown in Tie2-expressing cells restores regenerative lung growth in the aged mouse lungs. Since Tie2 is expressed in other cell types such as fibroblasts and immune cells, which also contribute to vascular and alveolar epithelial morphogenesis [ 69 ], Twist1 expression in these other cells may contribute to post-PNX lung growth in the aged lung. Twist1 knockdown in ECs in other organs may also indirectly affect post-PNX lung growth.…”
Section: Discussionmentioning
confidence: 99%
“…We used Tie2-specific Twist1 knockout mice in this study and found that Twist1 knockdown in Tie2-expressing cells restores regenerative lung growth in the aged mouse lungs. Since Tie2 is expressed in other cell types such as fibroblasts and immune cells, which also contribute to vascular and alveolar epithelial morphogenesis [ 69 ], Twist1 expression in these other cells may contribute to post-PNX lung growth in the aged lung. Twist1 knockdown in ECs in other organs may also indirectly affect post-PNX lung growth.…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary capillary microvascular niche in lungs supports alveolar epithelial repair mechanisms following injury, e.g. by secretion of MMP14, VEGF, thrombospondin-1 (THBS1) (Mammoto and Mammoto, 2019). Analysis of pulmonary endothelial cell subclusters revealed that bronchial, pulmonary capillary and pulmonary vein endothelial cells showed increased expression of Thbs1 at 5, but not 14 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…Human lung development can be histologically divided into four distinguishable stages: embryonic and pseudoglandular stages (human, week 4–17 and mouse, E9.5–E16.5), canalicular stage (human, week 17–26 and mouse, E16.5–E17.5), saccular stage (human, week 26–36 and mouse, E17.5–PN5), and alveolar stage (human, week 36–8 years and mouse, PN5–PN30) [ 46 , 47 ].…”
Section: Development Of Normal Pulmonary Vasculature and Bpd-ph Frmentioning
confidence: 99%
“…From E11 to E12, proximal vessels sprout from the main pulmonary trunk (proximal angiogenesis), run along the main conducting airways, as well as its many ramified branches. In addition, the distal blood islands increase markedly and are connected together to form the primitive capillary plexus (distal angiogenesis) [ 46 ]. During the late pseudoglandular stage, the capillary network, around lung buds, fuses with the proximal vessels.…”
Section: Development Of Normal Pulmonary Vasculature and Bpd-ph Frmentioning
confidence: 99%